Successful extirpation of a perforated esophagus after chemo radiotherapy in infiltrative ulcerative squamous cell carcinoma - T. S. Rogova; P. G. Sakun; Yu. A. Gevorkyan; S. G. Vlasov; L. Ya. Rozenko; S. A. Malinin; E. A. Karnaukhova; O. G. Rodionova; M. A. Komandirov; O. Yu. Kaimakchi; N. V. Soldatkina; E. A. Gorbunova (Южно-Российский онкологический журнал)
Esophageal cancer is one of the most aggressive malignant neoplasms of the gastrointestinal tract, occupying the eighth place in the structure of morbidity worldwide. Despite comprehensive approaches to treatment, mortality continues to grow in both gender groups, which moves this pathology to the sixth position in the structure of mortality from malignant tumors. A lot of patients undergo radiation therapy in the preoperative period or in an independent version due to the peculiarities of the localization of the tumor or the spread of the process. One of the serious complications of the disease on the background of ongoing conservative therapy is perforation of the esophagus, which, according to the literature, can develop from 5.6 to 33 % of cases, and the risk factors for the development of this complication are infiltrative-u lcerative form of cancer, disease stage T3–4 and the presence of esophageal stenosis, as well as the use of chemotherapy drugs such as fluorouracil and cisplatin. The article describes a clinical case of esophageal perforation in a patient with infiltrative-u lcerative form of squamous cell carcinoma of the esophagus on the background of preoperative chemoradiotherapy. The total focal dose (TFD) at the time of complication development was 24 Gy. As a result of a comprehensive additional examination, which revealed a developed complication in the form of perforation of the esophagus, an interdisciplinary council decided on an immediate surgical intervention, during which extirpation of the esophagus with gastro- and esophagostomy was performed. The patient was discharged on the 15th day in a satisfactory condition with a recommendation to conduct an IHC study for the presence of PD-L1 expression to determine further management tactics. This clinical case demonstrates the role of the infiltrative- ulcerative form of tumor growth, the stage of the disease, as well as the use of chemotherapy drugs during radiation treatment as risk factors for the development of esophageal perforation; an important task at the prehospital stage in the selection of such patients is a thorough examination in specialized oncological centers to exclude possible complications in the process of the above conservative treatment.